2019
DOI: 10.1029/2019jd030439
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Radio Spectrum of Thunderstorm Narrow Bipolar Events

Abstract: This paper reports a study to understand the radio spectrum of thunderstorm narrow bipolar events (NBEs) or compact intracloud discharges, which are powerful sources of high-frequency (HF) and very high frequency (VHF) electromagnetic radiation. The radio spectra from 10 kHz to about 100 MHz are obtained for three NBEs, including one caused by fast positive breakdown and two by fast negative breakdown. The results indicate that the two polarities of fast breakdown have similar spectra, with a relatively flat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(102 citation statements)
references
References 55 publications
11
88
2
Order By: Relevance
“…The current moment of each streamer was assumed to follow a function whose time derivative matches the shape of the NBP. Using these ideas, the authors of [28] managed to obtain a radio spectrum of NBPs which agrees with experimental observations.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The current moment of each streamer was assumed to follow a function whose time derivative matches the shape of the NBP. Using these ideas, the authors of [28] managed to obtain a radio spectrum of NBPs which agrees with experimental observations.…”
Section: Introductionmentioning
confidence: 58%
“…Recently, several attempts were made to model CID's as streamer bursts [25][26][27][28]. In [25,26], the CID is modeled as an interaction between two (or more) bipolar streamer structures formed in a strong large-scale electric field of a thundercloud and the features of the electromagnetic emission resulting from this interaction between streamer structures were examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately not much is known about the width of fast breakdown regions at the time of this writing, which leads to uncertainty in estimates of the lower bound of the background electric field. Liu et al () suggested that fast breakdown regions could be tens of meters wide, consistent with a small wfalse/L ratio of 0.1. Downward positive streamers in sprites, on the other hand, can fill a region with a wfalse/L ratio of approximately 1.0 although 0.5 is perhaps more typical (Stenbaek‐Nielsen et al, ).…”
Section: Numerical Simulationsmentioning
confidence: 99%